THE VALIDITY OF ONLINE MARRIAGE FROM A MAQASID SYARIAH PERSPECTIVE: JASSER AUDA'S SYSTEMIC APPROACH - Rachman Iqbal; Akbarizan Akbarizan (Yayasan Pendidikan Islam Almatani, 2025)
This study reveals the legality of online marriages, which are currently an alternative solution when the prospective bride and groom cannot meet in person. Technological advances in this digital era have become inevitable, thus becoming a topic of discussion in Islamic law. Online marriages are conducted via video calls, whether through Google Meet, Zoom, WhatsApp, or other applications, thus providing convenience for both parties who are separated by distance and location. This study uses a philosophical approach using the theory of maqashid sharia developed by Jasser Audha. The conclusion of this study is that, according to the perspective of maqashid sharia developed by Jasser Audha, the validity and permissibility of online marriages are a form of openness in Islamic law using a multidimensional method in addressing issues arising from global digitalization, referring to the six approaches in maqashid sharia. Thus, the permissibility of online marriages is in line with the achievement of the values of the features developed by maqashid sharia Jasser Audha.